id_ID id_ID: id_ID - Nawari, Ahmad; Sumarno; Firdaus, L.N.; Hadriana (Kementerian Sekretariat Negara Republik Indonesia, 2022)
This research aims to analyze the accuracy of the translation of Kampar Malay terms of address in a storybook entitled Mancaka from Kampar dialect to Indonesian. The research used the descriptive qualitative research method. Data for this study were terms of address collected from both the source and target texts of the folklore. The data were then analyzed by using a sociolinguistic approach to find out (1) terms of address and their functions, (2) translation procedures used to translate the terms of address, and (3) accuracy of the translation of the terms of address. The research findings revealed that 16 terms of address were found in the source texts, namely Mancaka, Yuong, Bujang, Kolen, Kami, Deyen, Kau, Ang, Waang, Awak, Mak, Amak, Nak Bujang Amak, Datuok, and Pandekar. In addition, 2 translation procedures were applied by the translator, namely conservation and cultural equivalence. Regarding the accuracy, no single deviation of meaning was found. Therefore, the translation of the terms of address in the book was very accurate. Keywords: terms of address, functions, procedure, and translation quality